Good administration and the Council of Europe law, principles, and effectiveness - Andrijauskaitė, Agnė (Oxford, United Kingdom New York, NY Oxford University Press, 2020)
ood Administration and the Council of Europe: Law, Principles, and Effectiveness examines the existence and effectiveness of written and unwritten standards of good administration developed within the framework of the Council of Europe (CoE) and in the case law of the European Court of Human Rights. These standards - called 'pan- European general principles of good administration' - cover the entire range of general organizational, procedural, and substantive legal institutions meant to ensure a democratically legitimized, open, and transparent administration respecting the rule of law. They are about the 'limiting function' of administrative law: its function to protect individuals from arbitrary power, to legitimize administrative action, and to combat0corruption. This book analyses the sources and functions of the pan-European general principles of good administration and seeks to uncover how deeply they are rooted in the domestic legal systems of the CoE Member States. It comprises 28 country reports dedicated to an in-depth exploration of the impact of these standards on the national legal systems of the Member States written by respective experts on these systems. It argues that the pan-European general principles of good administration lead to a certain harmonization of the legal orders of the Member States with regard to the limiting function of administrative law despite the many fundamental differences between their administrative and legal systems. It comes to the further conclusion that the pan-European general principles of good administration can be considered as a concretization of the founding values of the CoE and describes the 'administrative law obligations' a Member State entered into when joining the CoE.
Introduction Setting the scene for a 'true European administrative law' Ulrich Stelkens and Agnė Andrijauskaitė -- Sources and content of the pan-European general principles of good administration
Includes bibliographical references and index.
Keywords: Administrative law; European Union countries. -- Right to good administration; European Union countries -- Electronic books -- (OCoLC)fst01007141; Management; Right to good administration -- Council of Europe. -- European Union countries; Stelkens, Ulrich